Exploring stakeholder perceptions of marine management in Bermuda. (October 2017) - Lester, Sarah E.; Ruff, Elizabeth O.; Mayall, Kevin; McHenry, Jennifer
Abstract: Given competing objectives vying for space in the marine environment, the island of Bermuda may be an ideal candidate for comprehensive marine spatial planning (MSP). However, faced with other pressing issues, ocean management reform has not yet received significant traction from the government, a pattern seen in many locations. Spatial planning processes often struggle during the proposal, planning, or implementation phases due to stakeholder opposition and/or government wariness to change. Conflict among stakeholders about management reform has also proven to be a deterrent to MSP application in many locations. With these obstacles in mind, a detailed stakeholder survey was conducted in Bermuda to determine awareness, attitudes and perceptions regarding ocean health, threats to ocean environments, the effectiveness of current ocean management, and possible future changes to management. How perceptions vary for different types of stakeholders and how attitudes about specific concerns relate to attitudes about management changes were examined. Overall, the results indicate a high degree of support for spatial planning and ocean zoning and a high level of concordance even among stakeholder groups that are typically assumed to have conflicting agendas. However, attitudes were not entirely homogeneous, particularly when delving into details about specific management changes. For example, commercial fishers were generally less in favor, relative to other stakeholder groups, of increasing regulations on ocean uses with the notable exception of regulations for recreational fishing. Given the results of this survey, public support is likely to be high for government action focused on ocean management reform in Bermuda.